Some Physico-chemical Properties of Red Fruit Oil (Pandanus Conoideus Lam) from Hexane and Chloroform Fractions - Arumsari, Novita Inar; Riyanto, Sugeng; Rohman, Abdul (Fakultas Farmasi, Universitas Gadjah Mada, 2013)
As functional food oil, red fruit (Pandanus conoideus Lam) oil has been believed by local community to threat several degenerative diseases like cancer. Red fruit oil (RFO) has commanded high price value in Indonesian market. Therefore, the objective of the present study was to investigate several physico-chemical properties of RFO. Some parameters of RFO obtained from hexane and chloroform fractions have been evaluated. Such parameters include acid value, saponification value, anisidine value, conjugated dienes and trienes as well as p-anisidine value. Besides, absorptivity coefficient, fatty acid composition, and volatile compounds were also determined. Acid value and saponification value of RFO from chloroform fraction were higher than those in RFO from hexane fraction. In addition, RFO in hexane fraction has the higher iodine and anisidine values than that in chloroform fraction. Hexane is the best solvent to be used for analysis of RFO, as indicated by the highest absorptivity coefficient of RFO in hexane. The main fatty acid composed of RFO was oleic acid followed with palmitic acid. The main volatile compound present in RFO of hexane and chloroform fractions was 9-octadecenoic acid accounting of 41.57 % and 65.06 %, respectively.